Ciri Anatomi untuk Identifikasi Jenis-jenis Eleocharis (Cyperaceae) Pulau Madura - Ashari Bagus Setiawan; Nunik Sri Ariyanti (PTTI, 2018)
Ashari Bagus Setiawan & Nunik Sri Ariyanti. 2018. Anatomical Characters for Identifying the Eleocharis species (Cyperaceae) of Madura Island. Floribunda 5(8): 291–298. — Simple morphological vegetative structure of Eleocharis become an obstacle in identifying the species, especially when the specimen is sterile. Therefore, other valuable taxonomic evidences are needed in distinguishing the species. For this purpose, the Eleocharis species of Madura Island (E. atropurpurea, E. dulcis, E. geniculata, E. philippinensis, and E. spiralis) were compared based on the paradermal and cross sections of its culms. The results showed that those five Eleocharis species of Madura could be distinguished based on these anatomical characters of culms: length-width ratio of the epidermal cells, length ratio of the stomata l subsidiary cells to the guard cell, stomata l density, shape of the culm cross section, shape of the chlorenchyma cells, distribution of the vascular bundles and air cavities, presence of stellate parenchyma in the air cavities, and presence of parenchyma cells at the central pith. An identification key for the Madurese Eleocharis was constructed based on the anatomical characters of culms.Keywords: Anatomy of culms, Eleocharis, epidermis characters, Cyperaceae. Ashari Bagus Setiawan & Nunik Sri Ariyanti. 2018. Ciri Anatomi untuk Identifikasi Jenis-jenis Eleocharis (Cyperaceae) Pulau Madura. Floribunda 5(8): 291–298. — Ciri morfologi struktur vegetatif yang sederhana pada Eleocharis menjadi salah satu kendala dalam mengidentifikasi jenis-jenisnya, terutama jika spesimen dalam keadaan steril. Oleh karena itu, diperlukan ciri selain morfologi yang memiliki nilai taksonomi untuk membedakan antar jenisnya. Untuk itu, jenis-jenis Eleocharis asal Pulau Madura (E. atropurpurea, E. dulcis, E. geniculata, E. philippinensis, dan E. spiralis) dibandingkan berdasarkan sayatan paradermal dan melintang buluhnya. Hasil penelitian menunjukkan bahwa lima jenis Eleocharis Madura dapat dibedakanberdasarkan ciri anatomi buluh berikut ini: rasio ukuran panjang terhadap lebar dari sel-sel epidermis, bentuk sel penjaga pada stomata, rasio ukuran panjang sel tetangga terhadap sel penjaga pada stomata, kerapatan stomata, bentuk sayatan melintang buluh, bentuk sel-sel klorenkim, sebaran berkas pembuluh dan ruang udara, keberadaan parenkim bintang dalam ruang udara, dan keberadaan sel parenkim pada pusat empulur. Kunci identifikasi Eleocharis di Madura disusun berdasarkan ciri anatomi buluh tersebut.Kata kunci: Anatomi buluh, Eleocharis, ciri epidermis, Cyperaceae.